Aortic angioscopy assisted thoracic endovascular repair for chronic type B aortic dissection. Issue 1 (July 2020) - Nishi, Hiroyuki; Higuchi, Yoshiharu; Takahashi, Toshiki; Domae, Keitaro; Inoguchi, Keita; Kawasumi, Ryo; Hamanaka, Yuma; Komatsu, Sei; Hirayama, Atsushi; Kodama, Kazuhisa
Highlights: Non-obstructive general angioscopy is a modality to detect small areas in the aorta. All of the ulcer-like projections and entries were detected by non-obstructive general angioscopy. Based on the angioscopy findings, the range of the graft position was confirmed. Angioscopy was useful for observing the condition of the aortic intima. Angioscopy plays an important role to determine the precise position of the graft. Abstract: Background: Non-obstructive general angioscopy is a powerful modality for detecting areas in the aorta with vulnerable plaque, which are difficult to visualize using conventional diagnostic tools such as computed tomography (CT). The aim of the present study was to clarify the efficacy and usefulness of aortic angioscopy in patients with chronic type B aortic dissection scheduled for thoracic endovascular repair (TEVAR). Methods: Ten patients with chronic type B aortic dissection who underwent elective TEVAR were enrolled. Before starting the stent graft procedure, the aortic intima was observed by use of non-obstructive general angioscopy. Based on those findings, the range of the stent graft position was confirmed. Results: In all patients, observations of the aortic intima with non-obstructive general angioscopy from a point just proximal of the descending aorta to the iliac artery were successful. At the proximal site, an entry site or ulcer-like projection was detected in all patients, while a small intimal tear or entry, or an irregular intima surface with a salmon-pink color were seen in some cases. In contrast, preoperative CT did not detect any such findings in the same locations. After confirming the position of the abnormal intima, we determined the position of the distal end of the stent graft. No complications considered to be related to aortic angioscopy were noted. Conclusions: Non-obstructive general angioscopy is useful for observing the condition of the aortic intima, revealing abnormal conditions, and confirming a normal aortic intima in patients with chronic type B aortic dissection. This modality may play an important role in determining the precise position of a stent graft for a TEVAR procedure.